Lift and drag trend of exocoetus volitans model in the wind tunnel - Osrin A.F. (Springer Science and Business Media Deutschland GmbH, 2023)
Aerodynamic drag; Angle of attack; Antennas; Lift; Wind tunnels; Aero-dynamic performance; Aerodynamic characteristics; Aerodynamic force coefficients; Aerodynamic forces; Aerodynamic parameters; Angle-of-attack; Flying fish; Lift and drag; Lift and drag coefficients; Wind tunnel experiment; Fish